Swedish Literature in Russian Translation 1946–2021: Prose fiction, poetry and drama. - Podlevskikh Carlström, Malin (University of Gothenburg, 2023)
The data material contains editions (in book form) of Swedish literature published in Russian translation on Russian (and Soviet) publishing houses between 1946–2021. The data material aims to create a general overview of translation and publication of Swedish literature in Russia, and will form the basis for further analyses of the publication and reception of Swedish literature in Russia.

Data has been gathered using Swedish and Russian library resources (The Swedish Royal Library’s catalog Libris, the digital catalog of The National Library of Russia, and the digital catalog of The Russian State Library. Since neither catalog is complete, additional searches have been conducted on various literary webpages (livelib.ru, fantlab.ru), and web sites of Russian publishing houses.

Version 1 of the data material is restricted to editions of adult prose fiction, poetry and drama. Editions of non-fiction and children's literature will be added in following versions. Furthermore, Version 1 only includes a limited number of variables. A version containing more variables (about translators, types of translation, contents of anthologies etc.) will be published when the research project is finalized and the related articles have been published.

The data is available as an Excel file and as tab-separated text (.xlsx, .tsv).

Datamaterialet består av svensk litteratur utgiven i rysk översättning på ryska (och sovjetiska) förlag mellan 1946 och 2021. Datamaterialet inkluderar enbart publikationer i bokform (ej översättningar publicerade i tidskrifter). Datamaterialet syftar till att skapa en överblick över utgivningen av svensk litteratur i rysk översättning, och kommer att ligga till grund för kommande fallstudier gällande utgivning och reception av svensk litteratur i Ryssland.

Datamaterialet har samlats in med hjälp av den svenska bibliotekskatalogen Libris (Kungliga biblioteket) samt två ryska digitala bibliotekskataloger som tillhandahålls av det ryska statsbiblioteket i Moskva (RSL) och det ryska nationalbiblioteket i Sankt Petersburg (NLR). Då ingen av dessa kataloger är komplett har sökningar också gjorts på diverse webbplatscommunities om litteratur (livelib.ru, fantlab.ru, labirint.ru) och webbplatser tillhörande ryska bokförlag.

Version 1 av datamaterialet inkluderar enbart utgåvor av skönlitteratur för vuxna (prosafiktion, poesi och drama). Datamaterialet kommer allt eftersom att kompletteras med utgåvor av sakprosa samt barn och ungdomslitteratur i rysk översättning 1946-2021. Version 1 innehåller dessutom ett begränsat urval av variabler. En version med fler variabler (om översättare, översättningar, innehåll i antologier etc.) kommer att publiceras när forskningsprojektet är slutfört.

Data är tillgängliga som Excelfil samt som tabbseparerade textfiler (.xlsx, .tsv).
Svensk litteratur i rysk översättning 1946–2021: Prosafiktion, poesi och drama
Keywords: books; böcker; authors; författare; Swedish language literature; litteratur på svenska; Russian language; ryska; translations; översättningar; Languages and Literature; Språk och litteratur; Studies of Specific Literatures; Litteraturstudier